Observation of High-Valent Manganese(V)–Corrole Complexes During Metalation of meso-Functionalized A3-Corroles under Aerobic Conditions - Guntner, Armin; Faschinger, Felix; Aichhorn, Stefan; Müllegger, Stefan; Schöfberger, Wolfgang (Synlett, 2015)
We report the synthesis of alkoxy-functionalized Mn(III)–A3-corrole and Mn(V)–corrole complexes. Depending on the length of the alkoxy chain attached to the meso-tetrafluoropenyl moiety, the oxidation state of the central manganese ion could either be tuned to +III in case of O–C6 or O–C12 chains, or to +V in case of O–C18 chains. The Mn(V)–corrole displays metal-centered redox chemistry in solution. Reduction with SnCl2 or Ph3P leads to the clean conversion yielding the corresponding Mn(III) derivative.
Keywords: corrole; high-valent manganese complex; autooxidation; oxygen